Environmental restrictions of agricultural activities in the context of sustainable development of the territories of the Republic of Kalmykia - T. I. Bakinova; E. S. Kovanova; N. Ts. Pavlova (Юг России: экология, развитие, 2025)
The purpose of the article is to consider the role of environmental restrictions in the rational use of agricultural resources and to ensure sustainable development of rural areas of the Republic of Kalmykia.On the basis of aerospace observations, the degree of land degradation, pastures by the degree of compaction of pastures and changes in the area of open sands were assessed. Data on the number of main types of farm animals in farms of all categories and their impact on the pasture load and the quality of land were analyzed. The analysis shows that there are quite serious problems in the development of agricultural activities in the Republic of Kalmykia: the state of the land, desertification problems, lack of water reserves and the outflow of the working population.The analysis revealed the need to develop and implement scientifically based standards for the load of agricultural activities, i.e. environmentally acceptable standards, which will balance the socio-natural economic system of the region, especially as the principal industry is agriculture based on pasture resources.